Regulation Mechanisms of Plant Basic Leucine Zippers to Various Abiotic Stresses - Yu, Yan; Qian, Yuchen; Jiang, Mengyue; Xu, Jia; Yang, Jingting; Zhang, Tongyao; Gou, Liangpeng; Pi, Erxu (Frontiers in Plant Science, 2020)
The bZIP family is one of the most widely distributed and conserved transcription factor categories in eukaryotes. They are widely involved in processes of plant abiotic stress responses, such as improving the ability of plants to adapt to drought, salinity and cold. To comprehensively understand how plant bZIPs regulating these tolerances, this article will have an overview of their distributions on different species, characteristics of protein architecture, regulation mechanisms for target genes’ transcriptional expression, and relevant research progresses in recent years. Specially, we will discuss the possible roles of flavonoids, whose synthesis could be regulated by bZIPs, in abovementioned plant tolerant responses.